O tema do eremitismo na literatura conventual feminina : S. Paulo Eremita em A Preciosa de Soror Maria do Céu : dos relatos em prosa à narrativa épica - Morujão, Isabel (2002)
This work focuses on the figure of Saint Paul Hermit, as it appears in the epic poem of Soror Maria do Céu «Primaz do Ermo. S. Paulo Eremita», published in «A Preciosa. Obras de Misericórdia. Parte II», in 1733. Starting from an analytical and comparative retrospect of the hagiographic sources that deal with this model of hermit, the author seeks to establish the differences between the poem and its matrices, trying to evaluate how the heroic record works within the structure of the figure of the saint and its resultant message. The article attempts to capture the meaning that emerges from the passage of accounts in prose to epic narrative.